The Ruthenium‐Catalyzed Domino Cross Enyne Metathesis/Ring‐Closing Metathesis in the Synthesis of Enantioenriched Nitrogen‐Containing Heterocycles. Issue 27 (2nd June 2020) - Llobat, Alberto; Escorihuela, Jorge; Sedgwick, Daniel M.; Rodenes, Miriam; Román, Raquel; Soloshonok, Vadim A.; Han, Jianlin; Medio‐Simón, Mercedes; Fustero, Santos
Abstract : The tetrahydropyridine structure is present in a wide variety of natural and synthetic compounds with interesting pharmacological properties. Therefore, the search for new chemical routes capable of yielding this valuable nitrogen‐containing heterocycle is of utmost interest. Herein, we report the use of the ruthenium‐catalyzed ring‐closing enyne metathesis (RCEYM) and cross enyne metathesis/ring‐closing metathesis (CEYM/RCM) reactions of chiral nitrogen‐containing 1, 7‐enynes as an efficient route to synthesize a variety of enantioenriched tetrahydropyridine‐based conjugated 1, 3‐dienes. The RCEYM presented wide functional group tolerance and took place in moderate to high yields, with no significant differences when carried out on gram scale. These 1, 3‐dienes were suitable for further transformations, such as the Diels–Alder reaction, effectively yielding more complex enantioenriched bicyclic structures. Abstract : A family of chiral nitrogen‐containing 1, 7‐enynes was used as starting materials in the preparation of a variety of enantioenriched tetrahydropyridine‐based conjugated 1, 3‐dienes through ruthenium‐catalyzed ring‐closing enyne metathesis (RCEYM) and cross enyne metathesis/ring‐closing metathesis (CEYM/RCM) reactions.